OP021 Autologous haematopoietic stem cell transplantation for Crohn's disease: a retrospective study from the European Society for Blood & Marrow Transplantation (EBMT) Autoimmune Diseases Working Party. (16th January 2018) - Brierley, C; Castilla-Llorente, C; Labopin, M; Badoglio, M; Rovira, M; Ricart, E; Dierickx, D; Vermeire, S; Hasselblatt, P; Finke, J; Onida, F; Cassinotti, A; et al.
Abstract: Background: Autologous haematopoietic stem cell transplantation (AHSCT) is an emerging therapeutic option for refractory Crohn's disease (CD). The ASTIC trial of AHSCT failed to meet its stringent composite primary endpoint, but 1-year follow-up data demonstrate sustained efficacy. The real-world use and outcomes of AHSCT for CD are unknown. Using the EBMT registry, we evaluated long-term outcomes for patients undergoing AHSCT for CD in Europe. Methods: We searched the EBMT registry for patients aged >18 who received AHSCT for a primary diagnosis of CD between 1997 and 2015 outside the ASTIC study. Clinical data were obtained for 82 patients from 19 centres in 7 countries. Transplant and clinical outcomes were obtained from the treating clinician in each centre. Clinical response was categorised as remission (no abdominal pain and normal stool frequency), significant improvement (improved pain and frequency), no change, or worsening of symptoms. Results: Median age of patients was 30 years (range 20–65) and 63% were female. Median age at first diagnosis of CD was 17 years (range 2–53). Patients were heavily pre-treated, having failed a median of six previous lines of drug therapy (range 3–10) and 74% having had surgery. Median time from diagnosis of CD to AHSCT was 12 years (range 1–26). All patients received peripheral blood stem cells following conditioning with cyclophosphamide 200 mg/kg and 86% received anti-thymocyte globulin. Neutrophil and platelet engraftment occurred at a median of 10 days (range 6–22 and 1–44). Median follow-up was 41 months (range 6–174). At 100 days post-AHSCT, 64% patients were in clinical remission (CR) and a further 28% had experienced significant improvement. Five per cent had no reported change in disease, and 4% were worse than baseline. At 1-year post AHSCT, data were available for 76/82 patients. 43% were in CR, 20% improved, 17% unchanged, and 20% worsened. At last follow-up, 44% were in CR, 24% improved, 17% unchanged, and 15% worsened. Thirty-seven per cent required surgery post-AHSCT, and 73% re-started medical therapy. Of those requiring further treatment, 70% were re-sensitised to anti-TNF. Treatment-free survival, defined as survival without major surgery or medical therapy, was 27% and 22% at 3 and 5 years. There was one AHSCT-related death from sepsis at 56 days. Another patient died 8 years after AHSCT. Twenty-seven per cent developed an infection requiring treatment. A secondary autoimmune disease developed in 13%, most commonly thyroid disease (63%). Malignancy developed in 6%, of which skin cancer accounted for 60% of cases. Conclusions: This is the largest cohort of patients treated by AHSCT for CD reported to date. In this treatment-refractory population, 67% of patients had clinical disease improvement. AHSCT is a viable option for patients with treatment-refractory CD and further randomised controlled trials are warranted.